2023
DOI: 10.1111/gcb.16994
|View full text |Cite
|
Sign up to set email alerts
|

Ocean deoxygenation caused non‐linear responses in the structure and functioning of benthic ecosystems

Ludovic Pascal,
Joannie Cool,
Philippe Archambault
et al.

Abstract: The O2 content of the global ocean has been declining progressively over the past decades, mainly because of human activities and global warming. Nevertheless, how long‐term deoxygenation affects macrobenthic communities, sediment biogeochemistry and their mutual feedback remains poorly understood. Here, we evaluate the response of the benthic assemblages and biogeochemical functioning to decreasing O2 concentrations along the persistent bottom‐water dissolved O2 gradient of the Estuary and Gulf of St. Lawrenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 88 publications
(129 reference statements)
0
1
0
Order By: Relevance
“…Our results should be considered in the light of the current hypoxic conditions prevalent in the deep layer of the LSLE, where water oxygen levels are as low as 1 mg O 2 /L (Jutras et al, 2023). Under these conditions, it has been suggested that particle mixing and bioturbation of sediments may be nearly absent, likely in response to changes in infauna community assemblage and a lower metabolic activity (Pascal et al, 2023). In the water column, reduced degradation of organic matter by heterotrophic communities could occur at low oxygen concentrations leading to higher export at depth (Engel et al, 2017).…”
Section: Relationship Between Apparent Oxygen Utilization and Chlorin...mentioning
confidence: 77%
“…Our results should be considered in the light of the current hypoxic conditions prevalent in the deep layer of the LSLE, where water oxygen levels are as low as 1 mg O 2 /L (Jutras et al, 2023). Under these conditions, it has been suggested that particle mixing and bioturbation of sediments may be nearly absent, likely in response to changes in infauna community assemblage and a lower metabolic activity (Pascal et al, 2023). In the water column, reduced degradation of organic matter by heterotrophic communities could occur at low oxygen concentrations leading to higher export at depth (Engel et al, 2017).…”
Section: Relationship Between Apparent Oxygen Utilization and Chlorin...mentioning
confidence: 77%